2009
DOI: 10.1080/10934520903140033
|View full text |Cite
|
Sign up to set email alerts
|

Irrigation with treated wastewater: Effects on soil, lettuce (Lactuca sativaL.) crop and dynamics of microorganisms

Abstract: The aim of this study was to evaluate the applicability of treated wastewater for horticultural crops, assess the effects of continuous use of treated water on soil and crops, and analyse the physical, chemical and biological effects of irrigation with recycled water. Two lettuce plots watered with drinking water and treated wastewater were monitored over a three year period. Nutrients, heavy metal and the dynamics of pathogen and indicator microorganism content in soil and foliar tissues were analysed. Wastew… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(33 citation statements)
references
References 22 publications
3
30
0
Order By: Relevance
“…The soil pH values varied between 6.7 and 7.4. An increase of soil organic matter content through wastewater irrigation has also been reported by others (53)(54)(55)(56)(57)(58). This results in a rising microbial biomass and microbial activity (53,(59)(60)(61).…”
Section: Resultsmentioning
confidence: 78%
“…The soil pH values varied between 6.7 and 7.4. An increase of soil organic matter content through wastewater irrigation has also been reported by others (53)(54)(55)(56)(57)(58). This results in a rising microbial biomass and microbial activity (53,(59)(60)(61).…”
Section: Resultsmentioning
confidence: 78%
“…According to Kiziloglu et al (2007), wastewater has a high nutritive value that may improve plant growth, reduce fertilizer application rates, and increase productivity of poor fertility soils. Diverse studies have indeed shown that TWW irrigation increases soil organic matter (Mañas et al 2009;Jueschke et al 2008;Kiziloglu et al 2007) as well as the concentrations of different nutrients involved in plant growth such as nitrogen (N), phosphorus, iron, manganese, potassium, calcium, magnesium, and others (Akponikpe et al 2011;Rezapour and Samadi 2011;Sacks and Bernstein 2011;Mañas et al 2009;Gwenzi and Munondo 2008;Kim et al 2007; Kiziloglu et al 2007;Angin et al 2005). Conversely, the use of TWW for irrigation can have detrimental effects on soil quality.…”
Section: Wastewater Reuse In Agriculture: Benefits Vs Risksmentioning
confidence: 99%
“…Several studies have reported high count of total coliforms and fecal coliforms in crops irrigated with TWW (Akponikpe et al 2011;Sacks and Bernstein 2011;Mutengu et al 2007;Rai and Tripathi 2007), while others have detected bacterial pathogens such as Salmonella, Streptococci, Clostridium, Shigella, and Vibrio spp. (Mañas et al 2009;Samie et al 2009). Other human pathogens associated with wastewater reuse include helminthes, viruses, and protozoa (Carey et al 2004;Caccio et al 2003;Tree et al 2003).…”
Section: Wastewater Reuse In Agriculture: Benefits Vs Risksmentioning
confidence: 99%
“…Water has been iden-tified as a major reservoir for pathogens and irrigation as a vehicle for transmission of pathogens to fields and produce (12,30,41,(72)(73)(74)(75). L. monocytogenes is often found in various water sources, with reported prevalence from Ͻ1% to 29% (14,76,77).…”
Section: Field Practices Associated With Presence Of Pathogensmentioning
confidence: 99%
“…In particular, Salmonella prevalence of 6 to 9% has been reported for water samples obtained from produce-growing regions in California and New York State (14,23). Manas et al (30) determined that lettuce plants irrigated with nonpotable water had significantly higher rates of total coliforms and Salmonella contamination than lettuce irrigated with drinking water. A number of studies also have linked sporadic or repeated contamination events in produce fields to wildlife fecal deposits (21), with a variety of bacterial food-borne pathogens, including Salmonella and L. monocytogenes, regularly isolated from fecal samples collected from wildlife and domesticated animals (3,(31)(32)(33)(34)(35)(36).…”
mentioning
confidence: 99%